Health Resort Medicine Development in Perm Krai before and after COVID-19 Pandemic: a Retrospective Study - Matvei S. Oborin; Eugeniy V. Vladimirsky (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
AIM. To substantiate the prospects for health resort complex development in Perm Krai in terms of adaptation to the effects of the COVID-19 pandemic and the use of therapeutic base of resorts in the region in the recovery and rehabilitation process. MATERIALS AND METHODS. Statistical data on the health resort complex state of the region, as well as the dynamics of individual groups of diseases for 2017-2021 were used. The research was conducted on the basis of philosophical methods, comparison, grouping, description, modeling. RESULTS AND DISCUSSION. The health complex of Perm Krai is traditionally well-developed, it operates on a rich hydro-mineral resource base, which allows to diversify the therapeutic profile and implement programs for the recovery, treatment and rehabilitation of the population after COVID-19 with long-term negative consequences and exacerbation of chronic and concomitant diseases. Regional health resorts indexes as a whole correspond to the negative trend of quantitative decline, which became especially noticeable in 2020 with subsequent gradual recovery. The profitability of the resorts of Perm Krai remains high, which suggests positive prospects for maintaining the sufficient supply and its focus not only on the residents of the region. The practice of state management of resort medicine shows that its systematic economic and fiscal support is needed, only in this case it will be possible to achieve significant coverage of the population with rehabilitation programs. First of all, there is a need for a regional strategy of the health resort complex development with clearly defined program measures. This should be done taking into account the experience of past planning with an analysis of the reasons why many indicators were not achieved. CONCLUSION. Health resort complex of the region has a developed resource and infrastructure potential, experience, traditions that allow to implement programs for prevention and recovery of various categories of population after suffering from the disease caused by COVID-19. Diversified therapeutic profiles of resorts can become the basis for the formation of an advanced base of resort medicine in the region and the Volga Federal District.